2021
DOI: 10.1002/aur.2562
|View full text |Cite
|
Sign up to set email alerts
|

Communication and social interaction in the cannabinoid‐type 1 receptor null mouse: Implications for autism spectrum disorder

Abstract: Clinical and preclinical findings have suggested a role of the endocannabinoid system (ECS) in the etiopathology of autism spectrum disorder (ASD). Previous mouse studies have investigated the role of ECS in several behavioral domains; however, none of them has performed an extensive assessment of social and communication behaviors, that is, the main core features of ASD. This study employed a mouse line lacking the primary endocannabinoid receptor (CB1r) and characterized ultrasonic communication and social i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 134 publications
2
18
0
Order By: Relevance
“…Alterations in call clustering are paralleled by changes in acoustic features known to be important for categorical perception of ultrasonic vocalizations and are thus predicted to alter their communicative function and, consequently, the interaction between mother and pup [ 55 ]. Previous studies showed that call clustering is altered in multiple models with relevance to neurodevelopmental disorders, such as ASD [ 58 60 ]. Importantly, altered emission of isolation-induced ultrasonic vocalizations was detected despite intact maternal odor preference in the homing test.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in call clustering are paralleled by changes in acoustic features known to be important for categorical perception of ultrasonic vocalizations and are thus predicted to alter their communicative function and, consequently, the interaction between mother and pup [ 55 ]. Previous studies showed that call clustering is altered in multiple models with relevance to neurodevelopmental disorders, such as ASD [ 58 60 ]. Importantly, altered emission of isolation-induced ultrasonic vocalizations was detected despite intact maternal odor preference in the homing test.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some hyperactivity-related physiological changes, such as disturbed sleep in mutant mice, were not quantitatively measured. To fully assess the relationship between disruptive Ash1l mutations and autistic-like phenotypes in our mouse model, it is necessary to perform additional behavioral tests such as ultrasonic vocalizations, auditory startle responses, and direct social interactions in both young and adult animals ( Fyke et al, 2021a , b , c ). In addition, measurements of sleeping cycles by polysomnography are needed to quantify the disturbed sleep in mutant mice ( Tagaito et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…In experiment 1, both male and female B6 subjects were single-caged for the same time (72 h) in the test cage before each testing session to assess social behaviors and USVs: this allowed for us to assess sex differences in the same resident-intruder settings and pre-testing social isolation conditions. In experiment 2, the male mice were subjected to 10 min of isolation in the test cage, and their social behavior was compared with that of female mice exposed to 72-h pretesting isolation: this comparison served to evaluate sex differences under conditions that are commonly employed to assess male and female USVs in ASD mouse studies (Hebert et al, 2014 ; Pietropaolo et al, 2014 ; Oddi et al, 2015 ; Gaudissard et al, 2017 ; Gauducheau et al, 2017 ; Lemaire-Mayo et al, 2017 ; Fyke et al, 2021 ) and that are also more suitable for male behavioral assessment. USVs can in fact be also evaluated in male-female interactions without inducing a resident state in the male [e.g., Hebert et al, 2014 ; Oddi et al, 2015 ; Gaudissard et al, 2017 ; Lemaire-Mayo et al, 2017 ; Fyke et al, 2021 ], thus avoiding applying a social isolation period of at least 72 h that could interfere with several other behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Their USVs were compared with those of males that were either isolated for the same duration before testing (study 1) or only habituated to the testing cage for 10 min before tests (study 2). These two studies allow us to evaluate sex differences respectively (1) in the same resident-intruder settings, thus controlling for isolation effects and (2) using the most common (and practically more suitable) experimental settings for USV assessment used in previous studies with ASD mouse models, i.e., in the resident-intruder context for females and without pre-testing long isolation in males (Pietropaolo et al, 2011 , 2014 ; Hebert et al, 2014 ; Oddi et al, 2015 ; Gaudissard et al, 2017 ; Gauducheau et al, 2017 ; Fyke et al, 2021 ). In both studies, three subsequent social tests with a novel intruder were performed with an interval of 7–10 days in order to evaluate the potential stability of sex differences and their dependency on previous testing experience without confounding effects of social memory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation